TRANSPARANSI PELAYANAN PENYALURAN DANA ZAKAT PADA KANTOR BADAN AMIL ZAKAT PROVINSI SULAWESI UTARA - KIYAI, SYAHRIZAL; RARES, JOYCE; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2020)
Abstract: Transparency is a principle that guarantees access or freedom for everyone to obtaininformation about the administration of government, namely information about policies, the process ofmaking and results achieved, transparency is needed and required to be done in institutions or anypublic institution that has an interest in the public, Building transparency in the management of zakatwill create a good control system between two parties, namely institutions and stakeholders, because itdoes not only involve internal parties but also external parties. This research uses descriptive researchtype with a qualitative approach. Data collection techniques in this study used in-depth interviewtechniques with informants related to the research and also direct observation at the research locationand using literature study. The purpose of this research is to be able to describe how the transparencyof zakat fund distribution services at the office of the amil zakat agency in North Sulawesi province.Based on the results of the study it can be seen that the transparency of zakat services carried out by theamil zakat agency of North Sulawesi province has been done transparently, this can be seen from howthe North Sulawesi provincial baznas, provide so much access to information, both through applicationservices and directly , Baznas also often conducts the distribution process of zakat by inviting Muslimsfrom various groups to get involved, although it can be seen that the involvement of the people in termsof supervision and involvement in the distribution process of zakat is still lacking, this can be seen fromthe lack of understanding of Muslims towards the management process zakat. Therefore, supervisionand involvement of Muslims is needed for the management of zakat from the North Sulawesi provincialbaznaskeywords: transparency, management, service, zakat